(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
An experiment was conducted to find out the effect of essential oil percentage content and morphogenesis of Mentha piperita with foliar treatment of different concentration of zinc solution (1ppm, 1.5ppm, 2ppm, 2.5ppm, 3ppm and 3.5ppm as zinc chloride). An experiment was set up in earthen wear pots in three seasons of Bangladesh (winter, summer and monsoon). Zinc solutions were first applied as foliar treatment at 30days after planting, second and third treatment was applied after seven days intervals. Harvesting was carried out at 65 days after planting. In monsoon the maximum increase of leaves/hector (37.31 t /hector) with 3ppm Zn chloride solution and it was followed by summer (23.11t/hector) with 1ppm zinc chloride solution. 28.2% essential oil was increased compare with the control plant in summer with 3ppm zinc chloride solution; it followed by monsoon 6.7% essential oil when foliar treatment was 2.5ppm. Acid value, refractive index and density of oil were remaining more or less same in the whole period of the treatment. Key words: Mentha piperita, Planting time, Zinc chloride, Oil content quality, Plot yield. doi: 10.3329/bjsir.v44i1.2721 Bangladesh J. Sci. Ind. Res. 44(1), 125-130, 2009